2019
DOI: 10.1126/sciimmunol.aaw2004
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral activation of the necroptotic pathway components RIPK1 and RIPK3 potentiates antitumor immunity

Abstract: Although the signaling events that induce different forms of programmed cell death are well defined, the subsequent immune responses to dying cells in the context of cancer remain relatively unexplored. Necroptosis occurs downstream of the receptor-interacting protein kinases RIPK1 and RIPK3, whose activation leads to lytic cell death accompanied by de novo production of proinflammatory mediators. Here, we show that ectopic introduction of necroptotic cells to the tumor microenvironment promotes BATF3+ cDC1− a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
277
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(290 citation statements)
references
References 56 publications
10
277
3
Order By: Relevance
“…Although emerging studies demonstrate that MLKL-driven necrotic cell death promotes anti-tumour immunity (Brumatti et al, 2016;Snyder et al, 2019), whether GSDME-driven pyroptosis restricts tumour growth in vivo is still unclear and remains an open question. For example, a study reported that GSDME expression suppresses melanoma cell growth a murine xenograft model, whereas other studies documented that Gsdme deficiency had no impact on tumour formation during intestinal cancer Croes et al, 2019).…”
Section: Gsdme Activation By Caspase-3 Promotes Pyroptosis In Some Bumentioning
confidence: 99%
See 1 more Smart Citation
“…Although emerging studies demonstrate that MLKL-driven necrotic cell death promotes anti-tumour immunity (Brumatti et al, 2016;Snyder et al, 2019), whether GSDME-driven pyroptosis restricts tumour growth in vivo is still unclear and remains an open question. For example, a study reported that GSDME expression suppresses melanoma cell growth a murine xenograft model, whereas other studies documented that Gsdme deficiency had no impact on tumour formation during intestinal cancer Croes et al, 2019).…”
Section: Gsdme Activation By Caspase-3 Promotes Pyroptosis In Some Bumentioning
confidence: 99%
“…In support of this, cancer cell lines that express high levels of GSDME are extremely susceptible to pyroptosis after exposure of apoptosis‐inducing therapies such as cisplatin, doxorubicin and etoposide, while the same treatment triggers apoptosis in GSDME‐deficient or low expressing cells (Wang et al , ). Although emerging studies demonstrate that MLKL‐driven necrotic cell death promotes anti‐tumour immunity (Brumatti et al , ; Snyder et al , ), whether GSDME‐driven pyroptosis restricts tumour growth in vivo is still unclear and remains an open question. For example, a study reported that GSDME expression suppresses melanoma cell growth a murine xenograft model, whereas other studies documented that Gsdme deficiency had no impact on tumour formation during intestinal cancer (Zhou et al , ; Croes et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, DCs acquire high capability to migrate, to phagocytose dying cells, to process more efficiently caspase-cleaved cellular proteins (i.e., NM-neoAgs), and to cross-prime CD8 + T cells that can provide tumor control 35,38,41,42 , on the one hand, and immunopathology in various forms of chronic inflammatory diseases, on the other hand 37,[43][44][45][46][47][48] . In addition, several studies found that ICD synergizes with ICB therapy to further improve T cell responses against different tumors, proposing hence the hypothesis that ICD converts tumor cells into endogenous vaccine and boosts the ICB effects [49][50][51][52][53][54] . However, despite the large body of evidences on how ICD occurs, few evidences have been reported about the nature of antigens becoming immunogenic upon ICD 41,42 .…”
mentioning
confidence: 99%
“…We then examined the endogenous OVA-specific CD8 + T cell response using MHC-I peptide tetramers of SIINFEKL, referred hereafter as Tetramer (Snyder et al, 2019; Yatim et al, 2015). Tumors from Cd11c-Cre Rubcn flox/flox mice contained significantly more Tetramer + CD8 + T cells, indicating that Rubcn -deficient DCs are more efficient at cross-presentation of tumor-derived antigens (Figure 4H).…”
Section: Resultsmentioning
confidence: 99%